Pengaruh Cyber Public Relations Pada Event Festival Jajanan Bango 2022 Terhadap Brand Image Bango : Survei Pada Pengikut Akun Instagram @bangowarisankuliner - Fathur Rodzi Firmanto; Winda Dwi Astuti Zebua (STIKes Ibnu Sina Ajibarang, 2024)
In this era of globalization, rapid development of information technology and digitalization, the role of Cyber Public Relations in influencing brand image has become crucial to the success of companies. In this context,